E-LEARNING ADOPTION READINESS IN SECONDARY EDUCATION OF DEVELOPED AND DEVELOPING COUNTRIES: A SYSTEMATIC LITERATURE REVIEW - Ratu Syafianisa Nuzulismah; Harry Budi Santoso; Panca O. Hadi Putra (Universitas Trunojoyo Madura, 2022)
Situation in COVID-19 pandemic forced educational activity to shift from face-to-face to blended learning or to full online learning. This situation becomes a problem in different academic levels, especially secondary education as some teachers and students were not ready. This “E-Learning Adoption Readiness in Secondary Education: A Systematic Literature Review” article summarized the influencing factors and issues of readiness in adopting e-Learning in high school, including the technologies and communication tools, as the foundation of analysis. The research objective is to identify and compare e-Learning adoption between developed and developing countries during pandemic. This article used Kitchenham and Charter method which extract data research published in databases such as Scopus and Science Direct. This research found distinct gaps between developed and developing countries in the context of e-learning readiness adoption and factors that influenced the said adoption. We conclude that there are still a numbers of basic internal and external factors that need to be considered in e-Learning adoption, especially in developing countries. The implication and recommendation for the adoption during pandemic is hoped to be insightful for future research in the same field, as there are significant differences in developing and developed countries, especially regarding IT literacy.